2021
DOI: 10.21763/tjfmpc.788871
|View full text |Cite
|
Sign up to set email alerts
|

Aile Hekimliği Polikliniğine Başvuran Hastaların Geleneksel ve Tamamlayıcı Tıp Uygulamaları Hakkında Bilgi ve Davranışları

Abstract: Objective: To determine the knowledge and behaviors of the patients applying to family medicine clinic in a rural area about traditional and complementary medicine (TCM) applications. Methods: This is a descriptive cross-sectional study. A 13-question survey, created by the researchers, was applied to the participants. The research was carried out in a family medicine clinic in B. district of A. province. Volunteers 18 years and above who agreed to participate in the study were included. For statistical analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
1
3
0
2
Order By: Relevance
“…In recent studies in our country, the frequency of use of TCM was found to vary between 14.8% and 59.1% [11,12,13,14,15]. In patients who applied to the physical therapy outpatient clinic, this rate was found to be 32.1% and 35.5% in two different studies [16,17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In recent studies in our country, the frequency of use of TCM was found to vary between 14.8% and 59.1% [11,12,13,14,15]. In patients who applied to the physical therapy outpatient clinic, this rate was found to be 32.1% and 35.5% in two different studies [16,17].…”
Section: Discussionmentioning
confidence: 93%
“…This may be due to having knowledge about different practices as the level of education increases [16,19]. The increase in the use of TCM with the increase in the level of education is found in different studies [11,14]. On the other hand, there are also studies stating that using TCM or non-medical practices as the rst choice and preferring these practices more are not related to education level [5,12,13,15].…”
Section: Discussionmentioning
confidence: 99%
“…In the researches, it is seen that the participants mostly know the bloodletting and cupping therapy. However, in the researches, it was determined that the participants knew the least mesotherapy, prolotherapy and homeopathy therapy 21,22 . In this study, it was seen that the participants were mostly known for bloodletting cupping and herbal medicine therapy, however, mesotherapy, prolotherapy and homeopathy was the least known.…”
Section: Resultsmentioning
confidence: 99%
“…Daha önce yapılan çalışmalarda da en sık başvurulan yöntemlerin başında kupa, fitoterapi, sülük yöntemleri gelmektedir. 20,21 Buna karşın, tıp fakültesi öğrencileri ile yapılan bir çalışmada en sık başvurulan yöntemin akupunktur olduğu, kupa yönteminin ikinci sıklıkta başvurulan yöntem olduğu, sülük uygulamasının ise hiç kullanılmadığı görülm- üştür. 22 Malezya'da yapılan bir çalışmada, akupunktur ve homeopatinin diğer yöntemlerden daha fazla kullanıldığı görülmüştür.…”
Section: Discussionunclassified